Money and Marriage: Saving for Future Use - Nayda I. Torres; Vervil Mitchell; Josephine Turner; Lisa Leslie; Michael S. Gutter (EDIS)
There are a lot of good reasons why you should save money. This revised 5-page fact sheet explains some of the benefits of saving and investing. Written by Nayda I. Torres, Vervil Mitchell, Josephine Turner, Lisa Leslie, and Michael S. Gutter and published by the UF Department of Family Youth and Community Sciences, April 2011.